Studies on production of biprotein from local vegetable waste - Prem Kumar A/L Ravindran (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
The significant increase demands for livestock product in recent years have influenced the important of protein as nutrient. Due to high cost of protein, exploration on finding an alternative protein source was done that do not conflict with the human and animal food production. So, the local vegetable waste was to be a potential for bioprotein production where it is enriched with high nutritional value, economically feasible and locally available. The production of bioprotein involves fermentation process which is solid state fermentation (SSF) of local vegetable waste with food fungi, Rhizopus oligosporus. Four types of vegetable waste were chosen for this research, which are corn waste, sugar cane waste, cucumber and bean sprout waste (black top skin). The screening part was aimed to identify which potential vegetable waste could produce higher bioprotein using microorganism (Rhizopus oligosporus). As a result, the highest protein production was showed by the bean sprout waste.